2007
DOI: 10.1080/10284150701284035
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal dietary supplementation with either gangliosides or choline: Effects on spatial short-term memory in artificially-reared rats

Abstract: This study addressed the hypothesis that dietary supplementation with either gangliosides or choline during the brain growth spurt would enhance short-term spatial memory. Male Long-Evans rats were reared artificially from postnatal days (PD) 5-18 and were fed diets containing either (i) choline chloride 1250 mg/l (CHL), (ii) choline chloride 250 mg/l and GD3 24 mg/l (GNG) or (iii) choline chloride 250 mg/l (STD). A fourth group (SCK) was reared normally. Rats were weaned onto AIN 93G diet and on PD 35 were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Exogenous, but not dietary, gangliosides and SA appear to be effective at promoting cognition in adult or aging models [ 29 , 30 , 31 , 32 , 33 ] and deficit (i.e., drug-induced amnesia, cortical lesions, malnourishment) models [ 34 , 35 , 36 ]. The impact on young, normal animals is mixed, but ganglioside and SA administration have shown both positive and neutral effects on cognition [ 31 , 37 ]. These studies provided preliminary evidence that exogenous SA improves cognition; however, there is less evidence that dietary gangliosides improve cognition in normative models (i.e., gangliosides are provided at physiological concentrations via the diet to healthy animals during typical development).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous, but not dietary, gangliosides and SA appear to be effective at promoting cognition in adult or aging models [ 29 , 30 , 31 , 32 , 33 ] and deficit (i.e., drug-induced amnesia, cortical lesions, malnourishment) models [ 34 , 35 , 36 ]. The impact on young, normal animals is mixed, but ganglioside and SA administration have shown both positive and neutral effects on cognition [ 31 , 37 ]. These studies provided preliminary evidence that exogenous SA improves cognition; however, there is less evidence that dietary gangliosides improve cognition in normative models (i.e., gangliosides are provided at physiological concentrations via the diet to healthy animals during typical development).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , the relationship between both short term and long term stimulation (behavioural training) and increased expression of brain gangliosides, particularly in the hippocampus, has long been known [ 92 , 93 , 94 ]. Although exogenous administration of gangliosides into normal or functionally compromised animals has resulted in inconsistent effects on memory, behaviour and learning, possibly due to compositional differences in the ganglioside, mode of administration and different age models (reviewed in [ 95 , 96 ]), some of the findings nevertheless support a positive impact of gangliosides on cognitive functions. Intracerebroventricular injection of GQ1b resulted in improved spatial learning and memory in rats [ 97 ] while high doses of bovine brain ganglioside (principally GM1a, GD1a, GD1b, GT1b) administered intraperitoneally improved learning ability and memory retention in neonatal, developing and aged rats [ 98 ].…”
Section: Gangliosides In Neuroplasticity and Memory Formationmentioning
confidence: 99%
“…In another study, ganglioside supplementation of the pre-weaning diet of artificially reared rats with CML (0.2% w/v of diet) had no effect on spatial short-term memory although the authors found the results inconclusive due to methodological considerations and in particular, lack of adequate controls. Notably, however, brain GD1b + GQ ganglioside content was significantly higher in naturally suckled pups [ 96 ]. Clearly, there are many variables to consider in design of animal trials which will adequately address the hypothesis, among them the developmental window within which gangliosides are likely to have the most impact, dose and duration of intervention and relevance in humans.…”
Section: Dietary Gangliosides and Cognitive Functionsmentioning
confidence: 99%
“…This includes obtaining more specific evidence regarding which nutrients should be provided, at what rate, in what mixtures, and by what means, to optimise the growth and development of these infants [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%